Budaya Organisasi Islami dan Perilaku Kerja Kolaboratif Guru di Lembaga Pendidikan Islam - Supianto; Dhiyaa’ Ulfah; Salfen Hasri; Sohiron (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Organizational culture plays a strategic role in shaping teachers' work behavior, especially in the context of Islamic educational institutions that prioritize religious values as the foundation for managing education. The challenge of teacher collaboration, which still tends to be individualistic, highlights the importance of strengthening an organizational culture based on Islamic values as the foundation for collective work behavior. This study aims to analyze the characteristics of an organizational culture based on Islamic values in shaping collaborative work behavior among teachers in Islamic educational institutions. The research employs a qualitative approach through a literature study by analyzing relevant scientific literature from 2020–2025 regarding organizational culture, Islamic education management, and teacher collaboration. The study's findings show that Islamic values such as trustworthiness (amanah), brotherhood (ukhuwah), deliberation (musyawarah), and justice serve as the foundation of organizational culture, promoting the creation of a conducive work environment, strengthening interpersonal trust, and fostering teachers' pedagogical and professional collaboration. This study contributes to strengthening the perspective of Islamic education management by emphasizing that an Islamic organizational culture functions not only as a normative guideline but also as an operational framework in developing sustainable collaborative work behavior among teachers.